2012
DOI: 10.1016/j.regsciurbeco.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Industrial agglomeration and firm size: Evidence from China

Abstract: This paper, by using annual surveys of manufacturing …rms from 1998 to 2005 in China, …rst documents a positive correlation between industrial agglomeration and …rm size, which is previously found in developed economies. Next, by using the instrumental variable estimations, we identify that industrial agglomeration has a positive and statistically signi…cant causal impact on …rm size. Finally, we …nd that …rms are more likely to become larger by locating with a number of larger …rms than with a larger number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 69 publications
0
81
0
Order By: Relevance
“…Previous studies on why an agglomeration occurs and how it benefits economic agents have been mainly based on the two perspectives (Rosenthal & Strange, 2004): the localization economies, which are the Marshallian externalities arising from a concentration of firms in a same industry; and the urbanization economies, which arise from an increase in city size that enables cross-fertilization of idea among diverse economic activities (Jacobs, 1969). While both industry concentration and city size were found to be associated with higher productivity, when assessed together, empirical evidences tended to support the localization economies more than the urbanization economies (for example, Henderson, 2003;Li et al, 2012). While this paper is primarily oriented toward the localization perspective, it goes beyond the concept by incorporating explicitly the agglomeration of upstream industries.…”
Section: An Overview Of Studies On Agglomerationmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies on why an agglomeration occurs and how it benefits economic agents have been mainly based on the two perspectives (Rosenthal & Strange, 2004): the localization economies, which are the Marshallian externalities arising from a concentration of firms in a same industry; and the urbanization economies, which arise from an increase in city size that enables cross-fertilization of idea among diverse economic activities (Jacobs, 1969). While both industry concentration and city size were found to be associated with higher productivity, when assessed together, empirical evidences tended to support the localization economies more than the urbanization economies (for example, Henderson, 2003;Li et al, 2012). While this paper is primarily oriented toward the localization perspective, it goes beyond the concept by incorporating explicitly the agglomeration of upstream industries.…”
Section: An Overview Of Studies On Agglomerationmentioning
confidence: 92%
“…For instance, Greenstone, Hornbeck, and Moretti (2010) found that the United States firms in counties which saw new openings of "Million Dollar plants" realized 12% higher productivity growth after 5 years vis-à-vis the firms in other counties. More recently, Li et al (2012) observed that Chinese firms are more likely to become larger by locating with a number of large firms than with larger number of firms. Therefore, agglomerations that include many large firms may reward larger favorable effects on a firm's productivity.…”
Section: An Overview Of Studies On Agglomerationmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by the previous researchers Li et al (2012) and Kang et al (2012), the industrial distribution and regional numbers of firms are direct functions of the market size and possible regional market access: Eq.4 explains the same concept by indicating the importance of comparative advantage, while dealing with the distribution of the manufacturing sector in a two-region model. Statement 1: if one region improves its market access, ultimately improves its home market endogenously and exogenously by reconsidering trade costs, the region will become more attractive for firms to locate, which further helps the region to extract its market power and size.…”
Section: The Equilibrium Conditionmentioning
confidence: 63%
“…The agglomeration of industrial activities has significant impacts on firm behavior and firm performance such as productivity (Ciccone & Hall, 1996;Drucker & Feser, 2012;Henderson, 2003), organization of production processes (Holmes, 1999;Li & Lu, 2009), innovation (Carlino, Chatterjee, & Hunt, 2007;Feldman & Audretsch, 1999), firm size (Li, Lu, & Wu, 2012), firm survival (Silva & McComb, 2012), destination economic performance (Fan & Scott, 2003), destination attractiveness (Jin et al, 2012), and destination industry dynamics (Frenken, Cefis, & Stam, 2011).…”
Section: Industrial Agglomerationmentioning
confidence: 99%